1996
DOI: 10.1007/bf02338288
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate during development in the turtle embryo: effect of temperature

Abstract: Growth and development can occur over a wide range of physical conditions in reptiles. Cardiovascular function must be critical to this ability. However, information on cardiovascular function in developing reptiles is lacking. Previous work indicated that in reptiles the effects of temperature on growth and metabolism are largely restricted to early development. This study examined whether the previously observed effects of temperature and different perinatal patterns of metabolism observed in amniotic verteb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 29 publications
5
42
0
Order By: Relevance
“…2). Although thermal acclimation might affect the rate of embryonic heart beats [as found in the snapping turtle, Chelydra serpentina (Birchard and Reiber, 1996)], most studies on this topic have concluded that the growth efficiencies and energetics of reptilian embryos show little evidence of thermal acclimation (Whitehead et al, 1992;Angilletta et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2). Although thermal acclimation might affect the rate of embryonic heart beats [as found in the snapping turtle, Chelydra serpentina (Birchard and Reiber, 1996)], most studies on this topic have concluded that the growth efficiencies and energetics of reptilian embryos show little evidence of thermal acclimation (Whitehead et al, 1992;Angilletta et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The physiological mechanisms that link developmental time to temperature are probably complex but the cardiovascular system is known to play a critical role in nutrient and oxygen delivery during embryonic development (Birchard and Reiber, 1996;Birchard and Deeming, 2004;Tazawa, 2005). When embryonic growth is accelerated by higher temperature, the cardiovascular system must deliver nutrients at an increased rate to fuel the faster growth.…”
Section: Introductionmentioning
confidence: 99%
“…5). f H fell slightly before and markedly after hatching in the snapping turtle, Chelydra serpentina, indicating the establishment of an effective vagal tonus on the heart, coincident with the onset of lung breathing (Birchard and Reiber, 1996). A number of turtles and tortoises lack cholinergic tone on f H until the time of hatching although cholinergic tonus was verified during the final 30% of embryonic incubation in snapping turtles (Alvine et al, 2013) (Fig.…”
Section: Reviewmentioning
confidence: 92%
“…4), but measurements of blood flow have only been conducted in embryonic alligators (Eme et al, 2011a). Embryonic heart mass has been suggested to be an index of stroke volume during reptilian development (Birchard and Reiber, 1996;Crossley and Altimiras, 2000) so that changes in heart mass, in combination with measurement of f H , may provide an index of the changes in cardiac output accompanying development, enabling study of its control.…”
Section: Reviewmentioning
confidence: 99%
“…a Q 10 effect) and induces thermal acclimation of heart rate (i.e. changes in Q 10 ) (Birchard and Reiber, 1996;Birchard, 2000;Du et al, 2010). Temperature-induced variation (or sex differences) in heart rate (f H ) and arterial blood pressure (P m ) could influence growth and metabolism through changes in tissue perfusion, gas exchange and nutrient/waste transport.…”
Section: Introductionmentioning
confidence: 99%